Posterior urethral stenosis after prostate cancer treatment: contemporary options for definitive management - Kahokehr, Arman A.; Peterson, Andrew C.; Lentz, Aaron C. (Translational Andrology and Urology, 2018)
Posterior urethral stenosis (PUS) is an uncommon but challenging problem following prostate cancer therapy. A review of the recent literature on the prevalence of PUS and treatment modalities used in the last decade was performed. A summative narrative of current accepted techniques in management of PUS is presented, and supplement with our own experience and algorithms.